Providers' Perspectives Related to Parents' Choice of Pediatric Provider of Record and Newborn Screening: A Qualitative Study - Tracy Lowe; Jessica Boyd; Lina Shu; Jane M. DeLuca (SAGE Publishing, 2023)
The pediatric provider of record has a significant role in newborn screening and maintaining infant health after birth. Procedural errors and delays in communication can hinder the identification of infants with critical illnesses or follow up of unsatisfactory NBS samples. For this study, key stakeholders, including nurses, physicians, and midwives were interviewed to understand how the pediatric provider of record is selected by parents and examine factors affecting the newborn screening education and processes in the perinatal period. Provider responsibilities, timing of parent education, and social determinants of health played a role in parents' choices of the pediatric provider. Investment in future intervention programs is needed for reducing the number of infants without a designated pediatric provider of record. Research is needed to understand social complexities and healthcare systems which affect parents' choices of pediatric providers and newborn screening processes to optimize clinical outcomes for infants.